Existence and Multiplicity Results for the Scalar Curvature Problem on the Half-Sphere 𝕊+3. (20th March 2014) - Yacoub, Ridha
Abstract : In this paper we deal with the scalar curvature problem under minimal boundary mean curvature condition on the standard 3-dimensional half-sphere. Using tools related to the theory of critical points at infinity, we give existence results under perturbative and nonperturbative hypothesis, and with the help of some "Morse inequalities at infinity", we provide multiplicity results for our problem.